Factors controlling macroalgae assemblages in a Southwest Atlantic coastal lagoon modified by an invading reef forming polychaete - Bazterrica, Maria Cielo (2013)
In the Mar Chiquita coastal lagoon (37° 40′S, 57° 23°W, Argentina), the invasive reef building polychaete 23 Ficopomatus enigmaticus, change the composition and abundance of macroalgae by providing habitat to 24 some species and by excluding others. The magnitude of these effects may be regulated by consumers and 25 nutrients availability. Here we evaluate the relative importance of consumers and nutrients in controlling 26 macroalgae development on the reefs, and on the sediment in areas without reefs. Experiments showed 27 that: (1) large consumers (birds, fishes and crabs) had no effect on red (Polysiphonia subtilissima) and 28 green (Cladophora sp.) macroalgae on reefs; (2) large consumers had positive effect on green macroalgae 29 development on the sediment of areas without reefs, probably by enhancing the availability of bivalve shells 30 for macroalgae attachment; (3) small consumers (amphipods, hydrobiid snails and crabs) had negative effect 31 on green macroalgae development, probably by direct consumption; (4) small consumers had positive effect 32 on the biomass of the red macroalga P. subtilissima; and (5) nutrient had no effect on macroalgae. These 33 interactions would determine the abundance and the spatial distribution of macroalgae (e.g., patchiness). 34 Consequently, the effect of an invader ecosystem engineer in the composition of species assemblages may 35 be mediated by other community structuring forces, which in turn may have different effects according to 36 their interaction with the invader.